A Review of Nutritional Content in Street Vendor Snack Food Around Maranatha Christian University Bandung: Review of Nutritional Content in Street Vendor Snack Food Around Maranatha Christian University Bandung - Susanto, Robby; Stefani, Shiela; Dani, Dani (Jurnal Medisci, 2024)
The rapid development of the times globally has caused changes in food consumption patterns, especially snacks in Indonesia. From studies and research conducted previously in 22 developing countries, the results of the high prevalence of students being overweight were obtained. The purpose of this study is to determine the nutritional content of street vendor snack food around Maranatha Christian University. In this study, an observational descriptive research design was used with a quantitative approach using primary data and sampling was carried out by convenience sampling. The parameters measured in this study were the content of macronutrients, especially carbohydrates, proteins, fats and total calories in a 100 g serving of food with a kilo calorie unit (kcal). The research was conducted from early January 2021 to November 2021. The average value of carbohydrate content was 30.3 g, protein 6.9 g, and total calories 248.3 kcal, while the fat content analysis used a median value of 9.2 g. The conclusion in this study was obtained 15 snacks high in carbohydrates, 13 high in fat, 1 high in protein, and 1 high in carbohydrates and fats which were determined based on the percentage value of macronutrient content to total calories.